1986
DOI: 10.1128/jvi.59.3.635-645.1986
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies virus gene encoding glycoprotein gIII is not essential for growth in tissue culture

Abstract: We have established that in the Becker strain of pseudorabies virus (PRV), the glycoprotein glll gene is not essential for growth in cell culture. This was accomplished by construction and analysis of viral mutants containing two defined deletion mutations affecting the glll gene. These mutations were first constructed in vitro and introduced into Escherichia coli expression plasmids to verify structure and protein production. Each mutation was then crossed onto PRV by cotransfection of plasmid DNA and parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 35 publications
(71 reference statements)
5
101
0
Order By: Relevance
“…These results obtained with HSV parallel results recently reported for the porcine herpesvirus pseudorabies virus (PRV) (32,35,36,40,47,50). For both viruses, it appears that gC and the gC homolog of PRV (gIll) are dispensable for viral propagation in cell culture and yet play an important role in the adsorption of virus to cells.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…These results obtained with HSV parallel results recently reported for the porcine herpesvirus pseudorabies virus (PRV) (32,35,36,40,47,50). For both viruses, it appears that gC and the gC homolog of PRV (gIll) are dispensable for viral propagation in cell culture and yet play an important role in the adsorption of virus to cells.…”
supporting
confidence: 82%
“…As mentioned in the Introduction, PRV encodes a homolog of gC (gIll) which also significantly enhances the adsorption of virus to cells, even though it is not absolutely essential for virion infectivity (36,40,47,50). In addition, it appears that PRV gIll (like HSV gC) mediates the adsorption of wild-type PRV to cell surface heparan sulfate inasmuch as heparin blocks the adsorption and infectivity of PRV, both virus and solubilized gIll have affinity for heparin-Sepharose, and treatment of cells with heparinase blocks adsorption and infectivity of PRV (32).…”
Section: Discussionmentioning
confidence: 99%
“…Southern blot analysis. To identify correct recombinant viruses, a Southern blot analysis was performed on viral DNAs as previously described (23). Viral DNAs were digested with PstI and probed with [ 32 P]pGBe4.3.…”
Section: Methodsmentioning
confidence: 99%
“…The initial step for many herpesviruses has been shown to include an electrostatic binding of virus particles to negatively charged cell surface heparan sulfate (17,18,20,32). This attachment is mediated principally by glycoprotein gC but has been found to be unnecessary, at least in cell culture, in that strains lacking their gC homolog are still infectious (10,19,23). Additionally, biochemical studies on several herpesviruses have demonstrated that gC and a second envelope glycoprotein, gB, are capable of binding to heparin, a species closely related to heparan sulfate (10,17,27).…”
mentioning
confidence: 99%
“…Pseudorabies virus (PrV), a herpesvirus of swine, encodes at least four glycoproteins that are not essential for growth in cell culture (2,12,18,21,22,26). Primary isolates of PrV, however, do express these glycoproteins; consequently, they must play a role in virus replication, at least in vivo.…”
mentioning
confidence: 99%